Cyclical properties of Moroccan migrant remittances: an empirical analysis - FARHI, SAMIR; EL BOUANANI, HICHAM (Statistics, Optimization & Information Computing, 2025)
Remittances constitute a major source of financing for most developing countries, due to their growing volume and their potential contribution to the growth and development of the countries of origin. Morocco is no exception to this dynamic. The literature on the cyclicality of these flows reveals that they can be procyclical or countercyclical. This cyclicality has major implications for economic and financial policies. A better understanding of these dynamics would make it possible to optimize the use of these funds in times of expansion as well as in times of crisis, thus strengthening their role as a stabilizer and shock absorber. In this context, this study analyzes the cyclicality of remittances to Morocco during the period 1980-2022, using appropriate econometric filters and a vector autoregressive model (VAR) incorporating impulse response functions (IRF), in order to study the interactions between these flows and economic cycles. This article argues that the cyclical nature of remittances must be assessed in a dynamic framework.